IMPROVING ENGLISH PRONUNCIATION WITH PHONETIC SYMBOLS: A CASE STUDY OF SECOND-SEMESTER STUDENTS IN THE ENGLISH DEPARTMENT AT INSTITUT AGAMA ISLAM DARUL A’MAL IAIDA LAMPUNG - Cromico, Jimmy (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
This study aims to investigate the effectiveness of using phonetic symbols in enhancing English pronunciation skills among second-semester students of the English Department at Institut Agama Islam Darul A’mal IAIDA Lampung. The research employed a quasi-experimental design, involving two groups: an experimental group that received treatment using phonetic symbols and a control group that was taught using conventional methods. Both groups were pre-tested and post-tested to measure their pronunciation abilities. The findings revealed a significant improvement in the pronunciation skills of the experimental group, as evidenced by the post-test results, compared to the control group. Additionally, students expressed a high level of interest in learning pronunciation through phonetic symbols, with the majority indicating strong engagement and appreciation for this method. The study concludes that phonetic symbols are an effective tool in improving English pronunciation and suggests that they be incorporated into pronunciation teaching methods to support students’ language learning experiences.